miR‐92a aggravates metabolic syndrome via KLF2/miR‐483 axis - Zhe Zhao; Chaofeng Ma; Longzhi Wang; Yuhang Xia; Jun Li; Wei Yang; Juan Pang; Hui Ding; Haifeng Wang; Liang Bai; Fenqing Shang; Feng Zhang (Journal of Diabetes Investigation)
ABSTRACT Objective To exam the role of miR‐92a/KLF2/miR‐483 in the pathogenesis of metabolic syndrome. Methods In this study, the serum of healthy controls and patients with metabolic syndrome were collected to detect the circulating level of miR‐92a and miR‐483. In vitro cultured HUVECs, overexpression or suppression of miR‐92a, miR‐483 or KLF2 to determine the relationship among miR‐92a, KLF2 and miR‐483. Ang II, ox‐LDL, or high glucose treatment were used to mimic the metabolic syndrome. HUVECs or HepG2 cells were treated with Telmisartan, Atorvastatin, or metformin, the miR‐483 and its target gene expression was detected. In animal experiment, ob/ob mice were chose to confirm the changes of miR‐92a, KLF2, and miR‐483. Results Compared with the healthy controls, the level of miR‐92a was significantly increased, while miR‐483 level was remarkably decreased in the patients with metabolic syndrome. In vitro cultured HUVECS, overexpression of miR‐92a significantly reduced the expression of miR‐483, but overexpression of miR‐483 had no effect on miR‐92a. Overexpression of KLF2 could downregulate miR‐483 level, while inhibition of KLF2 had the opposite effect. When HUVECs and HepG2 were stimulated with Ang II, ox‐LDL and high glucose, the expression of miR‐483 was significantly decreased and its target genes was increased. Anti‐miR‐92a could reverse the effect. Furthermore, Telmisartan, Atorvastatin, and Metformin significantly increased miR‐483 expression and decreased its target gene expression, which could be reversed by miR‐92a mimic. The level of miR‐92a was significantly increased in HepG2 cells, which were treated with exosomes derived from endothelial cells with miR‐92a overexpression. ob/ob mice showed the similar effects. Conclusions Endothelial dysfunction and fatty liver are critically involved in the pathogenesis of metabolic syndrome. MicroRNAs can mediate the cellular communication between vascular endothelial cells (ECs) and distal cell. Serum miR‐92a level was higher in metabolic syndrome patients than controls. KLF2 is the target gene of miR‐92a, which can increase the production of miR‐483, miR‐483 acts on its target genes CTGF, ET‐1, and β‐catenin to protect cell function. EC miR‐92a is secreted out of cells into the blood, circulates through the blood to the liver, and continues to exert its biological effects after being absorbed by hepatocytes. LNA‐miR‐92a administration reversed endothelial cell damage and fatty liver caused by metabolic syndrome by affecting the KLF2/miR‐483 pathway.